Hematopoietic Cell Transplant and Use of Massage for Improved Symptom Management: Results from a Pilot Randomized Control Trial. (9th February 2012) - Mehling, Wolf E.; Lown, E. Anne; Dvorak, Christopher C.; Cowan, Morton J.; Horn, Biljana N.; Dunn, Elizabeth A.; Acree, Michael; Abrams, Donald I.; Hecht, Frederick M.
Abstract : Background . Pediatric hematopoietic cell transplant (HCT) is a lifesaving treatment that often results in physical and psychological discomfort. An acupressure-massage intervention may improve symptom management in this setting. Methods . This randomized controlled pilot trial compared a combined massage-acupressure intervention to usual care. Children were offered three practitioner-provided sessions per week throughout hospitalization. Parents were trained to provide additional acupressure as needed. Symptoms were assessed using nurses' reports and two questionnaires, the behavioral affective and somatic experiences scale and the Peds quality of life cancer module. Results . We enrolled 23 children, ages 5 to 18. Children receiving the intervention reported fewer days of mucositis (Hedges' g effect size ES = 0.63 ), lower overall symptom burden (ES = 0.26 ), feeling less tired and run-down (ES = 0.86 ), having fewer moderate/severe symptoms of pain, nausea, and fatigue (ES = 0.62 ), and less pain (ES = 0.42 ). The intervention group showed trends toward increasing contentness/serenity (ES = + 0.50 ) and decreasing depression (ES = − 0.45 ), but not decreased anxiety (ES = + 0.42 ). Differences were not statistically significant. Discussion . Feasibility of studying massage-acupressure was established in children undergoing HCT. Larger studies are needed to test the efficacy of such interventions in reducing HCT-associated symptoms in children.